Neural entrainment via perceptual inferences. (3rd March 2022) - Tavano, Alessandro; Maess, Burkhard; Poeppel, David; Schröger, Erich
Abstract: Entrainment depends on sequential neural phase reset by regular stimulus onset, a temporal parameter. Entraining to sequences of identical stimuli also entails stimulus feature predictability, but this component is not readily separable from temporal regularity. To test if spectral regularities concur with temporal regularities in determining the strength of auditory entrainment, we devised sound sequences that varied in conditional perceptual inferences based on deviant sound repetition probability: strong inference (100% repetition probability: If a deviant appears, then it will repeat), weak inference (75% repetition probability) and no inference (50%: A deviant may or may not repeat with equal probability). We recorded EEG data from 15 young human participants pre‐attentively listening to the experimental sound sequences delivered either isochronously or anisochronously (±20% jitter), at both delta (1.67 Hz) and theta (6.67 Hz) stimulation rates. Strong perceptual inferences significantly enhanced entrainment at either stimulation rate and determined positive correlations between precision in phase distribution at the onset of deviant trials and entrained power. We conclude that both spectral predictability and temporal regularity govern entrainment via neural phase control. Abstract : Predictability‐based perceptual inferences increase entrainment to isochronous auditory sequences. Both temporal and spectral regularities contribute to sensory entrainment